The geoecological aspects of bacteriocoenosis in Volga delta in conditions of anthropogenic load - L. V. Lartseva; O. V. Obuhova; A. A. Istelueva (Юг России: экология, развитие, 2015)
Long-term sanitary-microbiological monitoring indicated persistence and domination of opportunistic bacteria of the families Enterobacteriaceae, Pseudomonadaceae and Vibriona-ceae in water and among hydrobionts which is indicative of unsatisfactory sanitary characteristics of the species under study. Most of the isolated microflora showed various degrees of pathogenicity and multiple resistances to antibiotics. This is suggestive of epidemiological importance of isolated microorganisms.